A Case of Heterotopic Ossification in Papillary Renal Cell Carcinoma Type 2 - Facundo Davaro; Elizabeth Davaro; Amna Qureshi; Lindsay Lombardo (Case Reports in Urology)
Renal cell carcinoma (RCC) is associated with a variety of different histopathologic subtypes in which each subtype may be further subclassified. These entities carry with them unique prognoses and necessitate treatment with specific immunotherapy agents should advanced disease be uncovered. Meanwhile, aberrant physiologic processes may lead to unique histologic findings within these subtypes, further complicating management and prognostication. Heterotopic ossification within RCC is one of these rare occurrences and was once thought to have favorable prognostic implications. We report a case of a young female with papillary type 2 RCC with heterotopic ossification.